2016
DOI: 10.1155/2016/2473234
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Conbercept Pretreatment before Vitrectomy in Proliferative Diabetic Retinopathy

Abstract: Purpose. To determine the efficacy and safety of preoperative intravitreal conbercept (IVC) injection before vitrectomy for proliferative diabetic retinopathy (PDR). Methods. 107 eyes of 88 patients that underwent pars plana vitrectomy (PPV) for active PDR were enrolled. All patients were assigned randomly to either preoperative IVC group or control group. Follow-up examinations were performed for three months after surgery. The primary bioactivity measures were severity of intraoperative bleeding, incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 28 publications
(27 reference statements)
1
45
0
Order By: Relevance
“…Relatively few studies have been performed on the intravitreal injection of conbercept for the treatment of neovascularization in PDR. Some studies have focused on preoperative conbercept pretreatments and found that it could be an effective adjunct to vitrectomy by reducing the chances of intraoperative bleeding, accelerating postoperative vitreous clear-up and helping stabilize visual acuity restoration for PDR 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have been performed on the intravitreal injection of conbercept for the treatment of neovascularization in PDR. Some studies have focused on preoperative conbercept pretreatments and found that it could be an effective adjunct to vitrectomy by reducing the chances of intraoperative bleeding, accelerating postoperative vitreous clear-up and helping stabilize visual acuity restoration for PDR 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to aflibercept, conbercept (Kanghong Biotechnologies), the newest VEGF Trap, is a recombinant fusion protein composed of the second Ig domain of VEGFR1 and the third and fourth Ig domains of VEGFR2 fused to the constant region of human IgG1, and it acts as a receptor with affinity to all informs of VEGF and PlGF [ 5 7 ]. Preoperative conbercept treatment also allows patients with PDR to undergo surgery more quickly, with less risk of intra- or postoperative bleeding, and to have better postoperative BCVA [ 12 , 13 ], but the mechanisms are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, intravitreal conbercept (IVC) is better than posterior subtenon triamcinolone acetonide for diabetic macular edema in the proliferative stage of PDR [ 11 ]. Preoperative conbercept treatments also allow patients with PDR to undergo surgery more quickly, with less risk of intra- or postoperative bleeding, and result in a better postoperative BCVA [ 12 , 13 ]. Moreover, conbercept and ranibizumab are effective in the treatment of diabetic macular edema, with similar clinical efficacy, but conbercept has a longer treatment interval and fewer IVC injections are needed [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, have reported the opposite effects [12][13][14]. Conbercept (Chengdu Kanghong Biotech Co., Ltd., Sichuan, China) is a type of anti-VEGF agent, which has been widely used for curing patients with agerelated macular degeneration (AMD) and macular edema and has been reported to be an effective adjunct when injected before vitrectomy for PDR [15]. The aim of the present study was to investigate the role of conbercept in the prevention of postoperative vitreous hemorrhage when injected at the end of vitrectomy for severe PDR.…”
Section: Introductionmentioning
confidence: 99%